Schooling, Income and Social Position in Different Countries - Odaci Luiz Coradini, (IJRDO - Journal of Social Science and Humanities Research, 2019)
This article is the result of a research whose object is the differentiated value given to formal education, depending on indicators of social position, center/periphery relations, and social capital. In so doing, it compares 13 center and periphery countries as its case studies. The general hypothesis is that this differentiated value includes socially explicit and categorized resources and principles of hierarchy, such as scholarly titles and others that are implicit or indirect, like identity cleavages, center/periphery relations, and social capital. However, it is not about social capital that is based on civic morality, but instead, on social capital that is implicit and whose efficacy depends on dissimulation. Since it is not possible to expose the set of results in one paper, this focuses particularly on the relationship between the differentiated value of education and the occupational categories and scholarly titles.